The effects of sodium citrate ingestion on 3,000-meter time-trial performance - Shave, R.; Whyte, G.; Siemann, A.; Doggart, L. (The Journal of Strength and Conditioning Research, 2001)
The effect sodium citrate ingestion had on 3,000-m running performance was examined. Nine elite multidisciplinary athletes (7 men and 2 women, age 27.8 ± 4.7 years, height 176 ± 11 cm, mass 70.9 ± 8.7 kg) completed two 3,000-m trials. The trials were double-blind and randomly assigned for sodium citrate (0.5 g;pdkg1 body mass) and for sodium (NaCl, 0.1 g;pdkg1 body mass). Split times, heart rate (HR), and 3,000-m completion times were measured. Blood samples were collected preingestion, pre-exercise, postexercise, and 10 minutes postexercise and analyzed for lactate concentration. Blood lactate (LA) was significantly higher (p < 0.05) for the sodium citrate trial, both postexercise and 10 minutes postexercise. No significant differences (p > 0.05) in HR were observed between trials. Performance time was significantly faster (p < 0.05) for the sodium citrate trial (610.9 ± 36.6 seconds) compared with the placebo trial (621.6 ± 31.4 seconds). Sodium citrate ingestion improved 3,000-m running performance in elite multidisciplinary athletes; however, the high potential for gastrointestinal distress likely precludes the use of sodium citrate as an ergogenic aid among athletes.